Detecção de mecanismos de resistência, propriedades adesivas e capacidade de formação de biofilmes de Klebsiella pneumoniae multirresistentes - Wincker Neto, Carlos Hugo Del Priore (2013)
During the last decades, K. pneumoniae has emerged as one of the most clinically significant pathogens, especially due to the high prevalence of strains producing extended spectrum β-lactamases (ESBL) and carbapenemases. The therapeutic options to treat these infections are constrained not only by this enzyme production, but also by the regular ability to form biofilms. The development of K. pneumoniae biofilms on the host tissue eventually protect the microorganisms from the action of antimicrobial agents and from the immune response, apart from driving the expression of virulence factors. Thus, the aim of this study was to detect mechanisms of resistance, adhesive properties and ability of multi-resistant K. pneumoniae clinical isolates to form biofilms. In the first stage of the study, 33 strains of K. pneumoniae with reduced susceptibility to carbapenems were isolated. By using phenotypic tests, 10 samples positive for the modified Hodge test were detected, suggesting the production of carbapenemases, and 2 strains manifested positivity for the synergic test with boronic acid, suggesting the production of KPC. When employing molecular techniques, such as polymerase chain reaction, the gene blaKPC was not detected, characterizing failure on the phenotypic detection of KPC. In the second stage of the study, 14 strains of multi-resistant K. pneumoniae were analyzed in order to verify the ability of biofilm formation, as well as adhesive/aggregative properties. Most of the strains analyzed presented low affinity to p-xylene, suggesting hydrophilic character, aside from strong affinity to the basic solvent ethyl acetate indicating acidic surface characteristics. It was also verified that the strains studied manifested high ability of biofilm formation and important adhesion in epithelial cells. The combination of all the characteristics studied may contribute to the survival of K. pneumoniae in the host and in the environment, as the organization of microorganisms in biofilms complicates the pharmacological treatment and favors its spread and multi-resistance.